Narrative preaching - yet another perspective - J. J. van Rensburg (Acta Theologica)
The theme of narrative preaching has been widely discussed for more than a decade. However, only recently did the interest in this form of communication of the gospel of Jesus Christ become apparent within the congregational context. Ministers increasingly find it necessary to adopt a new approach in preaching. This interest was particularly enhanced by the postmodern emphasis on a hermeneutic approach and the importance of narratives and metaphors. This article endeavours to stimulate further interest on an academic level by researching certain problems necessitating a warning against indulgence of narrative preaching without understanding its nature and challenges. The wrong approach may cause an abuse of narratives and a resistance against any attempt to communicate the gospel in this manner.